Integration and mobility of Eastern European migrants in Scotland - Sergei Shubin (Environment and Planning A, 2013)
This paper deals with theoretical and practical issues related to employment migration and integration of Eastern European migrants in Scotland. It draws on interdisciplinary approach to the collection and analysis, as well as conceptualisations of mobility and integration from economics and geography to propose a broader theoriization of integration that recognizes the changing migration trajectories of Eastern European migrants.